Assessment of the antifungal efficacy of whey fermentate alone or in combination with citrus extract to control Aspergillus flavus mold in semi-moist pet food for dogs - Kiprotich, Samuel; Dhakal, Janak; Rasmussen, Cynthia; Aldrich, Greg (Frontiers in Microbiology, 2023)
Semi-moist pet foods contain moisture levels ranging from 15% to 40%, making them ideal for mold growth and mycotoxin production. To control spoilage, synthetic mold inhibitors such as potassium sorbate have been used, but consumers prefer "natural" preservatives. Whey fermentate (WPF) is an efficient antifungal, but it requires large doses. Therefore, the objective of this study was to determine the antifungal effect of WPF alone or in combination with citrus extract oil (CEX) against Aspergillus flavus in semi-moist pet food. Nutritionally complete semi-moist pet foods were produced with WPF alone (0.25%, 0.5%, and 1.0% (w/w)) and in combination with CEX; 0.25% WPF+ 0.015% CEX, 0.25% WFP+ 0.15% CEX, 0.5% WPF+ 0.015% CEX, and 0.5% WFP+ 0.15% CEX (w/w). The negative control (NC) contained no antifungal additive and the positive control (PC) had potassium sorbate (0.1% w/w). The semi-moist pet food was thermally formed and was cut into 3cm×3cm square pieces. Individual food pieces were inoculated with 0.1 mL of Aspergillus flavus (ATCC 204304) to achieve a final concentration of 5.0 log CFU/piece. The inoculated pieces were individually incubated at 25°C. Fungal analysis was performed on day 3, 6, 9, 12, 15, 18, 21, 24, and 28 by surface plating on Potato Dextrose Agar (PDA) followed by incubation at 25°C for 72 h. The total log reductions were calculated by subtracting the initial inoculum from the final log counts on day 28. Higher log reductions of Aspergillus flavus (p <0.05) were observed when WPF at 0.25% and 0.5% was combined with 0.15% CEX compared to when 0.015% CEX was used individually. All treatments were different from the NC (p <0.05). Citrus extract at 0.15% potentiated the antifungal effect of WPF at 0.5% to give a similar log reduction (p >0.05) to WPF at 1.0% in the food. In conclusion, CEX potentiated the antifungal efficacy and reduced the dose of WPF required to control Aspergillus flavus in semi-moist dog food.